Synthesis and Cell Imaging of Graphene Quantum Dots from Konjac Glucomannan. Issue 46 (6th December 2021) - Kang, Huiting; Zhang, Lilei; Hu, Sheng; Guan, Lianxiong; Liu, Wei; Tian, Dating
Abstract: Green photoluminescent graphene quantum dots (GQDs) were synthesized from konjac glucomannan (KGM), which is a natural polysaccharide, by a one‐step hydrothermal method. The resultant GQDs were characterized by various methods such as elemental analysis, X‐ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, atomic force microscopy, high‐resolution transmission electron microscopy, X‐ray diffractometry, and particle size analysis. The photoluminescence properties of the products were evaluated by ultraviolet‐visible spectroscopy, Raman spectroscopy, and fluorescence spectrometry. The lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO) of the products were calculated and verified by cyclic voltammetry. A cytotoxicity test indicated that the GQDs prepared from KGM had good biocompatibility. Moreover, the GQDs had excellent cell imaging performance, which suggests that the resultant products are promising candidates for biomedicine. Abstract : Green graphene quantum dots (GQDs) were facilely synthesized from konjac glucomannan, which is a polysaccharide. The resultant GQDs had good biocompatibility and showed excellent photoluminescence properties. Moreover, the GQDs had potential applications in bioimaging, biosensing, and disease diagnosis.